Study of Brachial Plexus and Its Variations Including Roots, Trunks and Cords in Formalin Preserved Cadaveric Human Brachial Plexuses - Manu Gupta, Renu Mishra, Swati Yadav, Rajni (International Journal of Innovative Research in Medical Science, 2017)
Brachial plexus is a principal somatic nerve supplying upper limb. Variations involving brachial plexus are not uncommon and knowledge of same is important for anatomists, surgeons and radiologists.